Guyana - How Do You Know Where to Get the Information You Need? Determining Ethics Approval Requirements in a Developing Country - Song, Gloria (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
Determining the process for obtaining local research ethics approval, or whether such a requirement even exists, may not always be straightforward in the context of some developing countries where such information may not be easily accessible to overseas researchers. How far do a researcher's ethical obligations extend in determining whether there is a requirement for local research ethics approval, and what form this would take (e.g., institutional or centralised ethics review)? In other words, how far should a researcher be expected to go in seeking out local ethics approval, especially where such information is not readily available? As part of this discussion, this case study describes the steps that I took as the principal researcher, before I was able to reasonably conclude that no national ethics approval requirement existed in Guyana for my particular research, which involved interviewing justice service providers about the implementation of Guyana's Domestic Violence Act. Drawing on this experience, I discuss various considerations that an international development researcher should bear in mind when planning and conducting research that seeks to meet leading international norms of research ethics.